Drug‐refractory myasthenia gravis: Clinical characteristics, treatments, and outcome - Cortés‐Vicente, Elena; Álvarez‐Velasco, Rodrigo; Pla‐Junca, Francesc; Rojas‐Garcia, Ricard; Paradas, Carmen; Sevilla, Teresa; Casasnovas, Carlos; Gómez‐Caravaca, María Teresa; Pardo, Julio; Ramos‐Fransi, Alba; Pelayo‐Negro, Ana Lara; Gutiérrez‐Gutiérrez, Gerardo; et al. (Annals of clinical and translational neurology, 2022)
Objective To describe the clinical characteristics and outcomes in patients with refractory myasthenia gravis (MG) and to determine the effectiveness and side effects of the drugs used for their treatment. Methods This observational retrospective cross‐sectional multicenter study was based on data from the Spanish MG Registry (NMD‐ES). Patients were considered refractory when their MG Foundation of America post‐interventional status (MGFA‐PIS) was unchanged or worse after corticosteroids and two or more other immunosuppressive agents. Clinical and immunologic characteristics of drug‐refractory patients, efficiency and toxicity of drugs used, and outcome (MGFA‐PIS) at end of follow‐up were studied. Results We included 990 patients from 15 hospitals. Eighty‐four patients (68 of 842 anti‐acetylcholine receptor [AChR], 5 of 26 anti‐muscle‐specific tyrosine kinase [MusK], 10 of 120 seronegative, and 1 of 2 double‐seropositive patients) were drug refractory. Drug‐refractory patients were more frequently women (p < 0.0001), younger at onset (p < 0.0001), and anti‐MuSK positive (p = 0.037). Moreover, they more frequently presented a generalized form of the disease, bulbar symptoms, and life‐threatening events (p < 0.0001; p = 0.018; and p = 0.002, respectively) than non‐drug‐refractory patients. Mean follow‐up was 9.8 years (SD 4.5). Twenty‐four (50%) refractory patients had side effects to one or more of the drugs. At the end of follow‐up, 42.9% of drug‐refractory patients (42.6% of anti‐AChR, 100% of anti‐MuSK, and 10% of seronegative patients) and 79.8% of non‐drug‐refractory patients (p < 0.0001) achieved remission or had minimal manifestations. Eighty percent of drug‐refractory‐seronegative patients did not respond to any drug tested. Interpretation In this study, 8.5% of MG patients were drug‐refractory. New more specific drugs are needed to treat drug‐refractory MG patients.